Uso de toxina botulínica tipo A en el manejo de dolor crónico refractario a tratamiento. Reporte de una serie de casos - Miranda M., Ana Luisa; Alfaro C., Roberto (Revista Hospital Clínico Universidad de Chile, 2015)
Introduction: Botulinum toxin type A (BTA) has analgesic effect independent of its action in muscle tone, inhibiting the release of neurotransmitters (substance P-glutamate) and neuropeptides of nociceptors. Objective: To characterize infiltration procedures with Botox® in patients with chronic pain refractory to treatment. Method: Observational-cross-retrospective study. Infiltrations with botox procedures performed in Hospital Clínico Mutual de Seguridad, between 01.01.2014 and 30.04.2015 were analyzed. Medical record data were extracted. Information analyzed with Excel2013® using Chi-square test (p <0.05). Results: 31 patients treated, 83.9% male. Average age 51 years (SD ± 11.9yo). Diagnostics causes of pain: posttraumatic pain and myofascial syndrome (25.8%); complex regional pain syndrome (16.1%) and partial hand amputation (12.9%). Predominant type of pain: neuropathic pain (64.5%). Common procedures: median nerve blockade (21.2%) and infiltration of lumbar back trigger points (15.4%). 77.4% reported good pain control, crisis decreased 74.2% and 71% decreases opioid use. Return work was effective in 64.5% of patients. 93.6% satisfactorily tolerated the procedure, 9.7% showed fewer adverse effects. The subgroup neuropathic pain had significantly worse results regarding mixed pain subgroup (p <0.05). Discussion: In this study, the use of BTA in chronic pain proved to be a safe and effective procedure for the management of chronic musculoskeletal pain.